Desemprego tecnológico no Brasil : um estudo da indústria de transformação à luz das idéias de Ricardo, Marx e Keynes (1990-2008) - Freitas, Carlos Eduardo de (2010)
John Maynard Keynes, contradicting the marginalist school dominant in his time, presented a new theory of employment which definitively linked the volume of employment in an economy with the bulk of its production: production increasing, simultaneously raised the volume of employment. The English economist noted that developments in technology could lead to technological unemployment: the production could increase by using a smaller amount of manpower. The issue of technological unemployment was a cause for concern by two of the greatest thinkers in the field of economic science: David Ricardo and Karl Marx. Both believed that the introduction of new machines could bring about chronic unemployment for a certain period of time. However, this was only a possibility, which had already taken place within English industrial capitalism, but which could be avoided if new investments absorbed the workforce laid off by the introduction of new machinery. Contrary to the views of these authors, renowned economists like J.B. Say, John S. Mill, and Alfred Marshall claimed that the introduction of modern machines temporarily dismiss certain amount of labor, but soon this volume of unemployed would be absorbed into new occupations, thus not occurring the technologically driven unemployment, this theoretical formulation was called the Compensation Theory. Brazil, in turn, passed during the 1990s through a period of restructuring of its industrial park, and through the methodology used in our study we verified that this was a determining factor for the existence of technological unemployment for much of this decade.